Novel galanin receptors in teleost fish: identification, expression and regulation by sex steroids - Martins, Rute S. T. (2014)
In fish, the onset of puberty, the transition from juvenile to sexually reproductive adult animals, is triggered by the activation of pituitary gonadotrophin secretion and its timing is influenced by external and internal factors that include the growth/adiposity status of the animal. Kisseptins have been implicated in the activation of puberty but peripheral signals coming from the immature gonad or associated to the metabolic/nutritional status are also thought to be involved. Additionally, there is evidence that the galaninergic system in the brain and testis of pre-pubertal male sea bass is a possible mediator involved in the translation of somatic signals leading to gonadal maturation. Here, the transcripts for four galanin receptors (GALR), named GALR1a, 1b, 2a and 2b, were isolated from European sea bass, Dicentrarchus labrax. Phylogenetic analysis confirmed the previously reported duplication of GALR1 in teleost fish, and unravelled the duplication of GALR2 in teleost fish and in some tetrapod species. Comparison with human showed that the key amino acids involved in ligand binding are present in the corresponding GALR1 and GALR2 orthologues. Transcripts for all four receptors are expressed in brain and testes of adult fish with GALR1a and GALR1b abundant in testes 15 and hardly detected in ovaries. In order to investigate whether GALR1 dimorphic expression was dependent on steroid context we evaluated the effect of 11-ketotestosterone and 17β-estradiol treatments on the receptor expression in brain and testes of pre-pubertal males. Interestingly, steroid treatments had no effect on the expression of GALRs in the brain while in the testes, GALR1a and GALR1b were significantly up regulated by 11KT. Altogether, these results support a role for the galaninergic system, in particular the GALR1 paralog in fish reproductive function.